Human Capital Investment, Knowledge Sharing, and Innovation Performance in Indonesian Service Companies - Dimas Arya Wicaksono; Nabila Fitri Handayani (Journal of Economics and Management, 2025)
This study examines the relationships between human capital investment, knowledge sharing, and innovation performance in Indonesian service companies. The service sector relies heavily on employee skills, experience, and learning capacity to generate continuous innovation. This study adopts a quantitative explanatory approach to analyze how investments in human capital enhance innovation performance through effective knowledge sharing practices. Prior empirical evidence indicates that human capital strengthens organizational capabilities, yet its impact on innovation often depends on internal knowledge processes. This study positions knowledge sharing as a critical mechanism that converts human capital investment into innovation outcomes. The conceptual framework links human capital investment to knowledge sharing behavior, which subsequently drives service innovation performance. Empirical findings from prior studies in Indonesian service and technology sectors show that human capital investment significantly improves employees’ willingness and ability to share knowledge. Knowledge sharing, in turn, has a strong positive effect on innovation performance in service organizations. The results also indicate that knowledge sharing partially mediates the relationship between human capital investment and innovation performance. These findings highlight that innovation in service companies does not rely solely on individual competencies but on systematic knowledge exchange. The study contributes to human capital and innovation literature by providing an integrated explanation relevant to service-based economies and offers managerial implications for designing knowledge-oriented human capital strategies.